2016
DOI: 10.1002/2016ja022633
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking equatorial plasma bubbles

Abstract: The formation of equatorial plasma bubbles (EPBs) associated with spread F irregularities are fairly common phenomenon in the postsunset equatorial ionosphere. These bubbles grow as a result of eastward polarization electric field resulting in upward E × B drift over the dip equator. As they grow they are also mapped to low latitudes along magnetic field lines. The EPBs are often observed as airglow depletions in the images of OI 630 nm emission. On occasions the growth of the features over the dip equator is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 63 publications
(85 reference statements)
1
23
2
Order By: Relevance
“…[] and followed in Narayanan et al . []. The results discussed herein are based on the observations from Panhala (16.8°N, 74.1°E; 11.1°N dip latitude) on 6 January 2008 and 3 and 5 February 2008 and those from Gadanki (13.5°N, 79.2°E; 6.5°N dip latitude) on 23 March 2009.…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…[] and followed in Narayanan et al . []. The results discussed herein are based on the observations from Panhala (16.8°N, 74.1°E; 11.1°N dip latitude) on 6 January 2008 and 3 and 5 February 2008 and those from Gadanki (13.5°N, 79.2°E; 6.5°N dip latitude) on 23 March 2009.…”
Section: Databasementioning
confidence: 99%
“…There have been reports revealing different directions of vertical plasma drift at different altitudes indicating pinching of the EPBs [ Laakso et al ., ]. On occasions, the EPBs were seen to shrink in their altitudinal extent over the dip equator [ Narayanan et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Here we propose the SGDI as a very possible mechanism to cause bifurcation of airglow depletion. Moreover, the northern EIA crest usually moves southward at nighttime (e.g., Narayanan et al, 2014Narayanan et al, , 2016Sun et al, 2017). The bifurcation would be generated by the SGDI when the eastward polarization electric field works on a northward sharp plasma gradient co-determined by the passing low plasma density within the airglow depletion of MSTID and the NPDE.…”
Section: Discussionmentioning
confidence: 99%
“…The MBWs frequently occur at the geographic equator, propagating poleward or equatorward and causing a reversal/abatement of meridional neutral winds (e.g., Colerico & Mendillo, 2002). The MBWs can also hold high plasma density to feed or erode the airglow depletions (e.g., Narayanan et al, 2014Narayanan et al, , 2016Sun et al, 2017). Thus the MBWs can be a source of NPDE.…”
Section: 1029/2018gl080926mentioning
confidence: 99%
“…Narayanan et al [] recently reported shrinking equatorial plasma bubbles. In their results, the poleward extension of the EPBs corresponds to the growth of the EPBs to higher apex altitudes and the equatorward collapse represents the shrinking of the EPBs toward lower apex height.…”
Section: Discussionmentioning
confidence: 99%